Biological determinants of P300 as mediators of its relationship with extraversion - Tatalović Vorkapić, Sanja; Tadinac, Meri (2007)
Introduction The aim of this study was to investigate the relationship between measures of the P300 (latency and amplitude), evoked by a standard visual oddball paradigm, and its biological determinants (age, use of glasses/contact lenses, consumption of coffee, cigarettes, medications, alcohol, illegal drugs, and sport activities) which were found to be significant in previous research (Polich, 1995) and to determine whether they mediate the relationship between P300 and personality dimension extraversion. It was expected that visual P300 would be affected by sight problems and, regarding the two measuring trials, it was expected that it would also be affected by other biological determinants although in different ways. Concerning the relationship between P300 and extraversion, it was expected that it would be mostly affected by the biological factors significantly correlating with either extraversion or P300 (age, sight problems, consumption of coffee, cigarettes, and medications). Materials & methods The sample consisted of 54 female psychology students, right-handers, age 19-23 years, with no history of neurological/psychiatric problems. The data on various biological determinants were collected by the General data questionnaire, and extraversion was measured by the Eysenck Personality Questionnaire (EPQ-R). The P300 responses were recorded in two trials for each subject using EMG/EP device Medelec/TECA SapphireII, 4E, in the Department of Neurology at CHC Rijeka. The active electrodes were two occipital (O1 and O2) and two parietal electrodes (P3 and P4), according to 10-20 system, and referred to Fz. P300 responses were elicited by the standard visual oddball paradigm. The subjects were instructed to look at the red circle in the center of the monitor and to react to the target stimuli by pressing the pen. Results The subjects wearing glasses showed significantly shorter P300-latencies. The significantly smaller P300-amplitudes in the second trial were found in older subject, those with no sight problems, those who drank coffee, did not use any medications, and did not smoke. Regarding the relationship between P300 and extraversion, the subjects who wore glasses, drank coffee, did not take medications and did not smoke showed a significant negative correlation between P300-latency and extraversion, while only those subjects who wore glasses showed significant negative correlation between P300-amplitude and extraversion. The regression analysis showed sight problems to be the best predictor of changes in P300-latency, while the best predictors of the changes in P300-amplitude were smoking, use of medication and sight problems. Conclusion The findings have confirmed the expected great sensitivity and variability in latencies and amplitudes of cognitive evoked brain potential P300 that should be taken into account in ERP research, especially when studying the relationship between P300 and personality.
Projekt MZOS
ENG